AN ANALYSIS OF READING MATERIAL IN “INTERLANGUAGE: ENGLISH FOR SENIOR HIGH SCHOOL X” TEXTBOOK PUBLISHED BY NATIONAL EDUCATION DEPARTMENT (RETAIN, 2014)
Abstrak Penelitian ini menggambarkan tentang analisi bacaan pada buku teks bahasa Inggris “Interlanguage: English for Senior High School X” untuk siswa kelas satu sekolah menengah atas. Untuk membantu peneliti menemukan analisi yang tepat dari bahan bacaan di dalam buku teks ini, penelitian ini merumuskan dua pertanyaan; Yang pertama mengenai relevansi bahan bacaan terhadap kurikulum 2006 dan yang kedua mengenai relevansi bahan bacaan terhadap criteria bahan bacaan yang baik menurut Nutal. Tujuan dari penelitian adalah untuk menggambarkan relevansi bacaan dalam buku teks bahasa Inggris terhadap kurikulum 2006 dan kriteria bahan bacaan yang baik. Peneliti berharap penelitian ini memberikan kontribusi yang berarti bagi para guru, penulis, pembaca dan peneliti selanjutnya. Penelitian ini fokus hanya pada buku teks bahasa inggris untuk siswa kelas satu SMA dan dibatasi pada keterampilan bahan bacaan. Desain penelitian ini adalah deskriptif kualitatif. Datanya berupa jumlah kalimat, kata-kata kompleks, dan suku kata dari bahan bacaan. Sumber datanya adalah bahan bacaan yang ada dalam buku teks bahasa Inggris. Data yang diperoleh dianalisis menggunakan lembar observasi dan catana lapangan, teks atau bahan bacaan dalam buku teks yang sesuai untuk kelas satu. Sementara iyu, dari analisis peneliti menyatakan bahwa enam bahan bacaan tersebut relevan dengan kurikulum 2006 dan dianggap sebagai materi bacaan yang baik. Hal ini menentukan bahwa bahan bacaan dalam buku teks yang relevan untuk siswa kelas satu SMA. Kata Kunci: Banan Bacaan, Buku Teks, Kurikulum 2006 Abstract This study is describing the analysis of reading materials in Interlanguage: English for Senior High School X textbook for senior high school X. To help the researcher to find the appropriate analysis of reading materials in a textbook, this study (it) formulates research questions are set up; 1. How is the relevance of reading materials in English textbook Interlanguage: to the Curriculum 2006, 2. How is the relevance of reading materials adapted from English textbook fulfill the criteria of good reading materials?. The purpose of this study is to describe the relevancy of reading materials in English textbook to the curriculum 2006 and to the criteria of good reading materials. The researcher expected this study gives the meaningful contribution for teachers, writers, the readers and the next researchers. This study only focuses on the English textbook for first graders of senior high school and concerns at the analysis of reading materials skill. The design of this study is descriptive qualitative. The data are the number of sentences, complex words, and syllables of the reading materials. The source of data is the reading materials in the textbook Interlanguage: English for Senior High School X. After all the data needed is collected, the next step is analyzing those data using field notes, the texts or reading materials in the textbook are appropriate for first graders. Since the textbook belongs to first graders, it can be stated that the texts or reading materials in the textbook should be relevant to the curriculum 2006 and considered as good text for the students of first grade to be used. From the analysis, the researcher found that all reading texts are relevant reading materials are relevant to the curriculum 2006 and considered as good reading text. It determines that the reading materials in the textbook are relevant to for first graders. Key Words: Reading Materials, Textbook, Curriculum 2006